Effective algorithm for building and solving linear systems - Serna, Sebastian Pena (2014)
Several mesh-based techniques in computer graphics such as shape deformation, mesh editing, animation and simulation, build and solve linear systems. The most common method to build a linear system consists in traversing the topology (connectivity) of the mesh, producing in general a representation of the set of equations in form of a sparse matrix. Similarly, the solution of the system is achieved, by means of iterating over the set of equations in the default sequence of the vertices (unknowns). This paper presents a new algorithm, which optimizes the build of the linear system and its storage, and which allows the iteration over the set of equations in any arbitrary order. Additionally, our algorithm enables rapid modiﬁcations to the linear system, avoiding a complete rebuild.